A critical systematic review assessing undergraduate neurology pipeline programs - Minen, Mia T.; Aymon, Ramisha; Yusaf, Ishah; Oza, Khushalee; Ekhtman, Jane; Katara, Aarti; Lebowitz, Naomi; Plovnick, Caitlin (Frontiers in Medicine, 2023)
Background Although current programs exist to encourage undergraduate interest in neuroscience and neurology, few students go on to pursue a career in neurology. Thus, there is a need for more neurologists in the US. To assess undergraduate pipeline programs and their goals of garnering interest and knowledge of neurology, we systematically reviewed available literature on existing undergraduate neurology pipeline programs. Methods A medical librarian conducted an electronic database search of PubMed, EMBASE, PsycINFO, Education Source, and ERIC based on a search strategy developed with a team of undergraduates and a neurologist. Of the 2852 articles screened, 33 met the systematic review criteria and were evaluated based on the type and goal of the pipeline program, its delivery, and efficacy. Results The 33 programs were classified into subtypes of pipeline programs, with focuses ranging from student-led projects to early clinical research opportunities. All programs were found to be successful in attracting student interest in neurology, providing exposure to relevant opportunities, and classroom enrichment. Discussion The existing literature shows that neurology pipeline programs successfully inspire interest in a career in neurology among undergraduate students. These programs are valuable supplements to undergraduate neuroscience curricula and instrumental in introducing students to various fields.